Quality control test of fixed x-ray units at Bir hospital and National trauma center - Adhikari, Kanchan Prasad; Nyaichyai, Kanchan Sarga; Chand, Birendra Bahadur; Khadka, Hanson; Sharma, Saroj; Khanal, Tara (Scientific World, 2022)
One of the important goals of the use of X-rays is to diagnose a disease and its extent and minimizing the adverse effect. In diagnostic X-ray, there is an important issue concerning the quality of the image and the exposure of radiation to the patient. Regular practice of quality control in diagnostic X-ray is essential to provide good quality images, decrease hazard to patients, and enhance the appropriate diagnosis. Quality control tests were carried out at six fixed X-ray units at National Academy of Medical Sciences, Bir Hospital and National Trauma Center. Parameters like kVp accuracy, timer accuracy, Reproducibility of kV, time and dose, variable mA and radiation output Linearity with the acceptance limits were checked. Radiation leakage, spatial resolution, contrast resolution and field alignment tests were also carried out. Quality control tests of kVp dose, dose rate, HVL, mAs, beam alignment and leakage radiation shows mixed results. The measured values were within limit in four X-ray units. Until now we do not have any regulations in Nepal on acceptance testing of x-ray units after installation. The need for quality assurance of X-ray needs to be taken to avert detrimental effects to patients and staff. Institutes must introduce a mandatory system for acceptance tests of X-ray when installed and alongside regular quality control programs.